2021
DOI: 10.1007/s12035-021-02440-8
|View full text |Cite
|
Sign up to set email alerts
|

Circulating lncRNAs HIF1A-AS2 and LINLK-A: Role and Relation to Hypoxia-Inducible Factor-1α in Cerebral Stroke Patients

Abstract: Long noncoding RNAs (lncRNAs) have been recently recognized as key players of gene expression in cerebral pathogenesis. Thus, their potential use in stroke diagnosis, prognosis and therapy is actively pursued. Due to the complexity of the disease, identifying stroke-speci c lncRNAs remains a challenge.This study investigated the expression of lncRNAs; HIF1A-AS2 and LINK-A and their target gene Hypoxiainducible factor-1 (HIF-1) in Egyptian stroke patients. It also aimed to determine the molecular mechanism impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…In this context, it was stated that down-regulation of HIF1A-AS1 could lessen ventricular remodeling and recover mice cardiac functions after myocardial I/R injury [ 41 ]. Concomitant with our result herein, a former study revealed a positive correlation between lncRNA HIF1A-AS2, HIF1-α, VEGF, and ANG1 in cerebral stroke [ 42 ].…”
Section: Discussionsupporting
confidence: 89%
“…In this context, it was stated that down-regulation of HIF1A-AS1 could lessen ventricular remodeling and recover mice cardiac functions after myocardial I/R injury [ 41 ]. Concomitant with our result herein, a former study revealed a positive correlation between lncRNA HIF1A-AS2, HIF1-α, VEGF, and ANG1 in cerebral stroke [ 42 ].…”
Section: Discussionsupporting
confidence: 89%
“…Five milliliters of venous blood were collected from each participant using BD Vacutainer ® SST II Gel collection tubes. The separated sera were aliquoted and frozen at −80 °C for the analysis of lncRNAs and gene expression levels [ 22 , 38 , 39 ]. An aliquot of the serum was used to assess TGF-β1 and IL-1β levels.…”
Section: Methodsmentioning
confidence: 99%
“…The RT reaction was incubated for 60 min at 37 °C, followed by 5 min at 95 °C. The produced cDNA was kept at −20 °C until analysis was conducted [ 22 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long noncoding RNAs (lncRNAs, longer than 200 nucleotides in length) fine-tune gene expression by recruiting epigenetic complexes or directly affecting transcription of multiple genes acting on various cellular paradigms 8 , 9 . The expression of lncRNAs is exceedingly controlled, with organ, tissue and even cellular specific patterns 8 , 10 and they have been documented to have crucial roles in the normal development, function, physiology, and pathophysiology of several endocrine organs such as the prostate, pancreas, and adipose tissue 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%